Screening of syphilis by rapid plasma reagin (RPR) and treponema pallidum haemagglutination assay (TPHA) method and determination of liver enzyme status in TPHA positive cases. - Pokharel, Mandira (2015)
ABSTRACT: Syphilis is a multi system infectious disease, remains asymptomatic in most of the cases but impose a great threat in public health, particularly among people of sexually active age group and pregnant women. Syphilitic hepatitis is a rare complication of primary and secondary syphilis with reversible cause of liver dysfunction . Very few studies are available showing the current trend on impact of syphilis in liver enzymes. This study was carried out to determine the prevalence of syphilis among the people visiting National Public Health Laboratory, Teku, Kathmandu and its association with liver enzymes. The detection of syphilis was done by screening test RPR and confirmatory test TPHA, level of liver enzymes was determined by blood test. In a total of 500 cases 28% were found to be positive, 18.2% was the case of active syphilis and 9.8% was the case of chronic syphilis. Titer values of RPR showed wide variation with 16.43% neat reactive and 12.86%, 17.4%,10.7%,5.71%,2.14% reactive at titer of 1:2,1:4,1:8,1:16 and 1:32 respectively . Among the total positives, almost 78% were married and 22% were unmarried . Prevalence of disease was seen higher in people of age group were unmarried . Prevalence of disease was seen higher in people of age group 21-25 years. there was no significant association between age distribution, sex, marital status and syphilis infection. A total of 9 liver enzymes were observed in syphilis positive cases, albumin and total bilirubin was elevated 17.07% and Gamma Glutamyl Transferase was elevated only in 3.65% of cases, whereas decreased values were seen only for Alkaline Phosphates and Lactate Dehydrogenase . All th 9 liver enzymes was found elevated in 2.5% of the total cases. Syphilis remains the great impostor and still must be considered in the differential diagnosis of unexplained liver enzyme abnormalities even in cases with no signs and symptoms of early syphilis. Keywords: Syphilis, Sero-prevalence, GAmm Glutamyl Transferase, Alkaline Phosphatase, Lactate Dehydrogenase.